STRUKTUR KOMUNITAS MESOFAUNA TANAH PEROMBAK BAHAN ORGANIK PADA VEGETASI KOPI DAN KAKAO - Erniyani, Kristina; Wahyuni, Sri; Puu, Yustina Maria Silvia Wonga (AGRICA, 2010)
The use of inorganic fertilizers and pesticides can change the agroecosystem gradually. These changes may result in a decrease in the diversity of soil organisms. These organisms are very important in the decomposition process of reforming the organic matter into compounds that are readily absorbed by plants. Other changes include a change in the soil structure which will affect the soil chemical and physical characteristic and ultimately affect the soil productivity leading to a decreased agricultural product. The return of the remains from harvest, litter and crop residues from coffee and cocoa crops to the soil will provide energy for soil organisms and it will help maintain the soil environment that supports the life of other organisms. This research aimed at identifying the composition and diversity of mesofauna formed by the composted organic matter in cocoa and coffee plantations. Soil sampling was conducted on coffee and cocoa plantations in the Onelako village of Ndona District. Soil sampling was conducted in September 2010. Soil sampling used Neuman method of 0-15 cm and 16-30 cm depth. Each soil sample was taken to the laboratory. The separation of mesofauna from soil used Berlese-tullgran method that had been modified for 4 days. The separated Meso fauna was identified under the light microscope. The result of this research showed that the highest composition of mesofauna decomposer of organic matter in cocoa and coffee vegetation is Collembola. Collembola is very tolerant to acidic soil condition and they are dominant in the soil and surface habitats that contain lots of litter. Collembola is microarthropods that have large distribution both in quantity and diversity. The highest diversity of mesofauna on coffee vegetation is 1.525 and on cocoa, vegetation is 1.273. It was also noted that at a depth of 0-15 cm there was a higher concentration of mesofauna in the coffee vegetation area, which was about 7.3960, while in the cocoa vegetation there where 3.6376. The high level of the diversity index caused an increase in decomposition and therefore better soil fertility.